2019
DOI: 10.25217/igcj.v2i1.242
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Islamic-Based Career Information Service to Improve Students Career Aspirations

Abstract: This study was based on the low career aspirations of the students' at senior high school of Muhammadiyah 1 Magelang, Indonesia and the lack of Islamic approach to improving career aspirations. Many students who did not have a career goal after graduating from high school. Otherwise, guidance and Counseling Teachers still use conventional career information services. The aim of this study is to determine the effectiveness of information services based on Islamic approach in improving career aspirations of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…which he chooses. (Nuraini et al, 2019) result of this research showed there was an improvement of the career aspirations of the student after receiving a career information service. (Ramdhani et al, 2018) The results of the study show that in general the career adaptability of students in Business Management Education is in the medium category with the character of students having concern, control, curiosity and confident, but there are still behaviors that do not reflect the four dimensions of career adaptability.…”
Section: Discussionmentioning
confidence: 81%
“…which he chooses. (Nuraini et al, 2019) result of this research showed there was an improvement of the career aspirations of the student after receiving a career information service. (Ramdhani et al, 2018) The results of the study show that in general the career adaptability of students in Business Management Education is in the medium category with the character of students having concern, control, curiosity and confident, but there are still behaviors that do not reflect the four dimensions of career adaptability.…”
Section: Discussionmentioning
confidence: 81%
“…This was explained in P. Nuraini's research that interventions using Islamic-based career information services can provide students with an understanding of how careers are in the Islamic view. Islamic-based career information services is a pattern that can be used by students as a form of implementation in career information service activities to enhance students' career aspirations towards a rules-based career that is applicable in the world and the rules of Allah SWT to obtain security and perceived benefits for themselves or for others [29].…”
Section: Discussionmentioning
confidence: 99%